The Influence Of Human Capital On Employee Work Produktivity At PT.Bank Sulselbar South Sulawesi - Insyafiah, Muh. Fakhriawan; S, Muh Rizal; Aslinda, Andi; Gani, Andika Wahyudi (Jurnal Administrasi Bisnis, 2025)
The Influence of Human Capital on Employee Work Productivity at PT. Bank SulselbarSouth Sulawesi. Thesis. Business Administration Study Program. Faculty of SocialSciences and Law. Makassar public university. Supervised by H.Muhammad Guntur andMuh.Rizal S.This study aims to find out how the influence of human capital on employeework productivity where Bank Sulselbar South Sulawesi is the object of research. Toachieve this goal, researchers use indicators to measure these variables. In the humancapital variable, the indicators used are knowledge, expertise, abilities, and skills. As forthe employee productivity variables, the indicators used are ability, work quantity, workquality, and attendance. In this study the research method used was quantitative research,with data collection techniques used through observation, questionnaires, anddocumentation. The sample used in this study was 93 respondents. The data obtainedfrom the results of the research were processed using data analysis and using the help of the SPSS version 25 program which consisted of validity tests, reliability tests, normalitytests, simple regression analysis, and the coefficient of determination.The results of the study show that the indicators used for each of these variables indicate that the human capital variable has a good or significant influence on the work productivity of employees at PT. Bank Sulselbar, South Sulawesi. This can be proven by testing the coefficient ofdetermination using the data that has been obtained.